PATTERNS AND CONSEQUENCES OF OBESITY ON CARDIOVASCULAR CONCERNS PREVALENCE, FLUCTUATIONS, AND HEALTHCARE DILEMMAS. - Yasra Memon; Sarah Elfituri; Prof. Dr. Anurag Rawat; Dr. Erum Fatima; Glory Aigbedion; Zubia Qayyum Chaudhary; Autif Hussain Mangi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Obesity has emerged as a pressing global health concern, with escalating prevalence rates. Objective: To assess the global prevalence, regional disparities, and associated healthcare implications of obesity. Methods: A comprehensive review of epidemiological data was conducted, focusing on regional patterns and demographic variations. Results: • Over 1.6 billion individuals surpass their ideal weight, with over 500 million categorized as obese. • Surprisingly high obesity rates are observed in historically undernourished regions, including Ibero-American countries, East Middle regions, Oceania, China, Australasia, Vietnam, and the Pacific Islands. • Africa and Asia exhibit notable obesity prevalences. • Obesity is implicated in over 300,000 annual deaths and incurs substantial healthcare costs. Conclusion: Obesity’s pervasive presence underscores the urgent need for targeted interventions and policy measures to address its multifaceted challenges.